Ribosome plasticity in glioblastoma: a multi-omics framework for future investigation - Benelli, Dario; Barbato, Christian; Cogoni, Carlo (Frontiers in Genetics, 2026)
Glioblastoma (GBM) remains a challenging tumour to mechanistically dissect, in part because of its capacity to adapt to hypoxia, metabolic imbalance and therapeutic pressure. Across cancer biology more broadly, attention has increasingly turned to ribosomal proteins (RPs). Although long regarded as stable structural components of the ribosome, several RPs show variation across tumour regions, stress states and differentiation trajectories. In some cancers, specific RPs have been mechanistically linked to selective translation or cell-state transitions, whereas in others the evidence remains largely associative. Overall, current observations leave open the question of whether RP variation reflects active regulatory roles or instead mirrors the broader physiological pressures experienced by malignant cells. In this mini review, we summarise what multi-omics approaches—including transcriptomics, proteomics and translatomics—currently reveal about RP regulation in GBM. Rather than making firm causal claims, we outline the main interpretations proposed so far, the uncertainties that complicate them and the conceptual gaps that keep the field open. Our aim is to provide a balanced and cautious overview that may help frame future work on how ribosomal components and the translational machinery could contribute to GBM plasticity.